ANALISIS KONSUMSI LISTRIK TERHADAP KESEJAHTERAAN DI SUMATERA BARAT DENGAN VARIABEL MEDIASI PENDIDIKAN DAN KESEHATAN - Digdaya Pramuda; Dewi Zaini Putri (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study explains the analysis electicity consumption on welfare district/cities in West Sumatra with mediation variable education and health. The method used is to a mediation regression model. This data uses a combination of panel data from 2013 - 2017, which consists of 19 city/districts. Data obtained from BPS annual report. The results of this study show that (1) Electricity consumption has a significant effect on welfare in West Sumatra (2) Electricity Consumption has a significant effect on education in West Sumatera. (3) Electricity Consumption has a significant effect on health in West Sumatera. (4) Education and health are able to mediate electricity consumption towards welfare in West Sumatra.